IbM PEGEMBANGAN KERAJINAN KAIN LUKIS DI JAWA TENGAH - I Nyoman Suyasa; Mardjono Mardjono; Eko Sri Haryanto (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
This Community Service Program activity aims to develop the ability of craftsmen in improving product quality and quantity. improve the competitiveness of the targeted partners in facing market challenges. The intended development includes; design, implementation of technology, marketing, strategy, and marketing materials. Partners of community service activities are Nasrafa located in Jebres Subdistrict, 2 kilometers from ISI Surakarta and Kaftan Art located in Mojolaban Sukoharjo Regency, Central Java Province, 6 kilometers from ISI Surakarta. The prospect of developing this handicraft product is very good and in demand by wide consumers, some have taken out of the country. The limited ability of human resources, business networks, and the limited equipment and dependence of the finishing process on the weather cause the partners are less able to take advantage of opportunities to develop this business with the maximum. After accompaniment, the partners are expected to be able to become more powerful craftsmen, so as to increase the production, design quality, to increase the selling value of the product, so as to increase the family’s income, then more to absorb the labor that comes from the surrounding community. Community service activities are carried out during the period of one year. The planned activities are; workshop on the use of production tools with appropriate technology, management training, and product design development workshops that are in demand by the market. After getting a touch of better painting design, proper management, modernization of production tools, attractive promotional media is expected to increase the competitiveness of partners in the face of the market.